Analysis of the shock response of UHMWPE composites using the inverse planar plate impact test and the shock reverberation technique. (December 2015) - Lässig, Torsten; Bagusat, Frank; May, Michael; Hiermaier, Stefan
Abstract: Ultra-high molecular-weight polyethylene (UHMWPE) composites are commonly used in ballistic protection systems. In order to understand the behavior under shock conditions, dynamic material properties were recently measured by inverse planar plate impact tests providing US –uP -data for particle velocities from 170 m/s up to 900 m/s. In this paper the previously known data range is extended at both ends. On the one hand, inverse flyer plate tests were performed at impact velocities less than 200 m/s in order to assess potential effects of porosity. On the other hand, the mechanical response under extremely high pressures was determined using the shock reverberation technique. For low shock pressures no effect of porosity was identified. For high shock pressures, the available data range was extended by a factor of 3. For the whole range of velocities and pressures, the slope of the US –uP relationship indicates a slight concave curvature. Highlights: The shock reverberation technique is described in detail. Inverse planar plate impact tests with UHMWPE were carried out. Investigations of the dynamic response of UHMWPE composite material at very high Hugoniot stresses. A hydrocode model for ultra-high molecular weight polyethylene has been validated for high velocity impact.